Vrijzinnigen hebben de toekomst - Meerten B. ter Borg (Religie & Samenleving, 2010)
The Future is for the liberals. In this essay the author tries to demonstrate that a liberal attitude is adequate to tackle the problems of the 21st century. The future is characterized by means of a number of trends that already exist, for instance: environmental problems, the shortage of basic materials, the shifts in the power structure, the ongoing globalization, the patterns of migration, etc. The way in which people choose to cope with these trends is, in all cases, dependent on their worldview. Here, the concept of liberalism is introduced. It is defined as an attitude that is, on the one hand, strictly focused on firm values and norms, but is, on the other hand, open towards alternatives. The first characteristic protects the worldview against relativism and anomy and the like; the second makes sure that it is flexible enough to adapt to the changing world.